RELATIONSHIP BETWEEN LENGTH OF STAY AND TOTAL STUDENT WITH SCABIES IN ISLAMIC BOARDING SCHOOLS IN BONDOWOSO - Siti Riskika; Sulistiawati Sulistiawati; Eka Mishbahatul (International Journal of Nursing and Health Services (IJNHS), 2019)
Scabies is a common contagious parasitic skin disease and a public health problem, mainly in tropical and subtropical countries. Scabies transmission occurs through direct and prolonged contact, and possibly through sharing contaminated clothing or bedding. Excoriation of lesions can lead to secondary bacterial superinfections. This study aimed to explain correlation between length of stay and total santri in one room in boarding schools. This study used a cross-sectional study with a chi-square method. The samples were 104 respondents recruited by simple random sampling, variable independent is total santri in one room and length of stay in boarding schools and variable dependent is an experience of scabies. Data analysis was performed and presented in descriptive statistics and chi-square tests. The results showed that the highest length of stay in boarding schools is more than two years 64 respondents (61.5%), the highest total santri in one room more than 30 people 72 respondents (69.2%), and santri with experience of scabies is 79 (76%). Chi-square test showed that correlation between total santri in one room and experience of scabies with p-value 0,01 (<0,005) that mean there is a significant relationship between total santri in one room with incidence scabies in santri, and chi-square test for correlation between length of stay in boarding schools and experience of scabies with p-value 0,00 (<0,05) that mean there is significant relationship between length stay of boarding schools and incidence of scabies in santri. There is a significant relationship between the long stay of boarding schools and total santri in one room with the incidence of scabies in santri. Keywords: scabies, santri, boarding schools